The Effectiveness of The Family Hope Program on The Welfare of Beneficiary Families in Banjarmasin City - Erna Suriyani (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
This study aims to determine the Effectiveness of the Family Hope Program (PKH) on the welfare of beneficiary families in Banjarmasin City. This study uses descriptive research, while the research approach uses qualitative. Data collection was conducted through in-depth interviews, observations, and documents. From the results of this study, the family hopes the program, seen from the knowledge of PKH beneficiary families towards the program's objectives, was adequate. The independence and behavior change of PKH beneficiary families in accessing education and health services has been evident. They are greatly helped by this program so that it can ease their burden, especially for children's education needs and in accessing health services for pregnant and lactating women and early children under six years. In the short term, this program is quite effective because it can reduce the expenditure burden on beneficiary families even though increasing their income is only limited to the program's assistance. In contrast, in the long term, namely, to break the chain of Poverty and inequality, it has not been effective and takes a long time. Therefore, it is necessary to add a skill component and business funding assistance for people experiencing Poverty in order to create independence and realize community welfare.